An Approach to Increase Power-Added Efficiency in a 5 GHz Class E Power Amplifier in 0.18 µm CMOS Technology - Hemad Heidari Jobaneh (IET Circuits, Devices and Systems)
A new approach to increasing the power-added efficiency (PAE) of a class E power amplifier (PA) is proposed in this paper. The PA operates at a 5 GHz frequency and a reactance compensation technique is utilized to maximize the bandwidth at the operating frequency. The driver stage creates either a half-wave rectified sine wave or a half-wave rectified sawtooth wave. By applying each one of the waves, the performance of the PA is examined and PAE = 70% and PAE = 50% is achieved. Plus, the output power of the PA is about 26 dBm when the DC voltage supply is 1.8 V. Advanced design system and TSMC 0.18 µm CMOS process are utilized to carry on the simulation.